Islamic Parenting In Islamic Education: A Study of Jamal Abdurrahman's Thought - Rafieudin, Muhammad; Madrah, Muna Yastuti; Choeroni, Choeroni (Universitas Islam Sultan Agung, 2025)
This study aims to examine the concept of Islamic Parenting from the perspective of Islamic education and analyze Jamal Abdurrahman's thoughts on child rearing based on Islamic values. The research method used is descriptive qualitative. Data collection was carried out using literature review, content analysis, and documentation methods. The results of the study show that Islamic Parenting is a process of child rearing based on Islamic values and centered on the teachings of tauhid as the main foundation of education. The instillation of tawhid from an early age is considered important to form a strong spiritual foundation, accompanied by the fulfillment of children's physical and spiritual needs. Parenting in Islam not only emphasizes physical aspects but also includes character building, worship habits, and instilling a love for the Qur'an and Sunnah to shape children's characters to be faithful and noble. In addition, Jamal Abdurrahman, in his work Aṭfālu al-Muslimīn Kaifa Rabbāhum an-Nabiyyu al-Amīn Ṣalallahu ‘Alaihi wa as -Salām, puts forward a concept of child education that is divided into five stages of development, infancy (0-3 years), childhood (4-10 years), early adolescence (11-14 years), late adolescence (15-18 years), and pre-marital age period. This division provides systematic guidance for parents and educators so that children's education can be optimally tailored to their stage of development and needs.